Redescription of Banyutus cubitalis (Navás, 1914) (Neuroptera, Myrmeleontidae) and key to antlion genera in tribe Nemoleontini from India - Suryanarayanan, Thangalazhi Balakrishnan; Bijoy, Chenthamarakshan; Ábrahám, Levente (Zootaxa, 2022)
The male and female of Banyutus cubitalis (Navás, 1914), a poorly known nemoleontid species from India was redescribed and illustrated based on the specimens collected for the first time from Southern Western Ghats (new faunistic records). Also, a key to the antlion genera in Nemoleontini tribe from India were provided.